Parents' Active Role and ENgagement in The review of their Stillbirth/perinatal death 2 (PARENTS 2) study: a mixed-methods study of implementation. Issue 3 (16th March 2021) - Burden, Christy; Bakhbakhi, Danya; Heazell, Alexander Edward; Lynch, Mary; Timlin, Laura; Bevan, Charlotte; Storey, Claire; Kurinczuk, Jennifer J; Siassakos, Dimitrios
Abstract : Objective: When a formal review of care takes places after the death of a baby, parents are largely unaware it takes place and are often not meaningfully involved in the review process. Parent engagement in the process is likely to be essential for a successful review and to improve patient safety. This study aimed to evaluate an intervention process of parental engagement in perinatal mortality review (PNMR) and to identify barriers and facilitators to its implementation. Design: Mixed-methods study of parents' engagement in PNMR. Setting: Single tertiary maternity unit in the UK. Participants: Bereaved parents and healthcare professionals (HCPs). Interventions: Parent engagement in the PNMR (intervention) was based on principles derived through national consensus and qualitative research with parents, HCPs and stakeholders in the UK. Outcomes: Recruitment rates, bereaved parents and HCPs' perceptions. Results: Eighty-one per cent of bereaved parents approached (13/16) agreed to participate in the study. Two focus groups with bereaved parents (n=11) and HCP (n=7) were carried out postimplementation to investigate their perceptions of the process. Overarching findings were improved dialogue and continuity of care with parents, and improvements in the PNMR process and patient safety. Bereaved parents agreed that engagement in the PNMR process was invaluable and helped them in their grieving. HCP perceived that parent involvement improved the review process and lessons learnt from the deaths; information to understand the impact of aspects of care on the baby's death were often only found in the parents' recollections. Conclusions: Parental engagement in the PNMR process is achievable and useful for parents and HCP alike, and critically can improve patient safety and future care for mothers and babies. To learn and prevent perinatal deaths effectively, all hospitals should give parents the option to engage with the review of their baby's death.